As desigualdades de Bohnenblust-Hille e Hardy-Littlewood - Almeida, Jonathas Phillipe de Jesus (2016)
In this study we show two classical inequalities, namely Bohnenblust-Hille inequality and Hardy-Littlewood inequality. The rst one, conceived as a tool for the study of problems related to Dirichlet series, is a generalization of Littlewood`s 4/3 inequality to multilinear forms. The second is a generalization of Bohnenblust-Hille inequality, produced by the replacement of c0 with lp.